European Mail Armour : Ringed Battle Shirts from the Iron Age, Roman Period and Early Middle Ages - Wijnhoven, Martijn A. (Amsterdam archaeological studies ;, 2022)
Mail armour (commonly mislabelled 'chainmail') was used for more than two millennia on the battlefield. After its invention in the Iron Age, mail rapidly spread all over Europe and beyond. The Roman army, keen on new military technology, soon adopted mail armour and used it successfully for centuries. Its history did not stop there and mail played a vital role in warfare during the Middle Ages up to the Early Modern Period. Given its long history, one would think mail is a well-documented material, but that is not the case. For the first time, this books lays a solid foundation for the understanding of mail armour and its context through time. It applies a long-term multi-dimensional approach to extract a wealth of as yet untapped information from archaeological, iconographic and written sources. This is complemented with technical insights on the mail maker's chaîne operatoire.